STRATEGI GURU UNTUK MENANAMKAN NILAI-NILAI PENDIDIKAN KARAKTER PADA PESERTA DIDIK: Studi Multi Kasus di The Naff Elementary School Kediri dan MI Manba’ul Afkar Sendang Banyakan Kediri - Arifin, Moh. Miftahul (LP2M IAIN Tulungagung, 2016)
Essentially, learning is an attempt to steer students into the learning process so that they can obtain learning objectives in accordance with what is expected. In the learning of an teacher need specific strategies, one of them to immers evalues, especially in the concept of character education. This study focuses on teachers’ strategies in immerse character take an object in two basic educational institutions: The Naff Elementary School Kediri and MI Manba’ul Afkar Sendang Banyakan Kediri. The result of this study is a strategy used-outline-learners familiarized with various types of habituation start of activities inthe classroom to outside classroom.Keywords: Strategy, Character Buliding, Education value